PENDEKATAN TEKNIK THOUGHT STOPPING DENGAN KONSELING INDIVIDUAL UNTUK MENGATASI KECEMASAN BERSOSIALISASI PADA WARGA BINAAN BARU DI LAPAS PEREMPUAN PALEMBANG: PENDEKATAN TEKNIK THOUGHT STOPPING DENGAN KONSELING INDIVIDUAL UNTUK MENGATASI KECEMASAN BERSOSIALISASI PADA WARGA BINAAN BARU DI LAPAS PEREMPUAN PALEMBANG - Widya Asmara; Sihabudin M. Amin; Noviza Neni (Jurnal At-Taujih, 2023)
The background of this study is that individuals who have high self-confidence can be said to be someone who respects himself. Every individual who has courage is able to make himself a person who can develop, be able to live life in the future, establish good relationships with other people without feeling afraid. This research uses a type of Field Research research, a qualitative approach, and uses a descriptive method. Aims to help with social anxiety by using thought-stopping techniques. This study uses data analysis techniques, namely data reduction, data presentation and drawing conclusions. Data collection techniques used are observation, interviews, and documentation. The results of the study obtained social anxiety from several subjects, namely having fear of the new environment, lack of confidence, and not being able to accept oneself. after the counseling process results, the client is able to control his social anxiety, the client has the courage to live a new life and is excited to live the future.